Photocatalysis and perovskite oxide-based materials: a remedy for a clean and sustainable future. Issue 12 (2nd March 2022) - Irshad, Muneeb; Ain, Quar tul; Zaman, Muhammad; Aslam, Muhammad Zeeshan; Kousar, Naila; Asim, Muhammad; Rafique, Muhammad; Siraj, Khurram; Tabish, Asif Nadeem; Usman, Muhammad; Hassan Farooq, Masood ul; Assiri, Mohammed Ali; et al.
Abstract : Photocatalytic reaction for CO2 reduction in presence of co-catalyst. Abstract : The massive use of non-renewable energy resources by humankind to fulfill their energy demands is causing severe environmental issues. Photocatalysis is considered one of the potential solutions for a clean and sustainable future because of its cleanliness, inexhaustibility, efficiency, and cost-effectiveness. Significant efforts have been made to design highly proficient photocatalyst materials for various applications such as water pollutant degradation, water splitting, CO2 reduction, and nitrogen fixation. Perovskite photocatalyst materials are gained special attention due to their exceptional properties because of their flexibility in chemical composition, structure, bandgap, oxidation states, and valence states. The current review is focused on perovskite materials and their applications in photocatalysis. Special attention has been given to the structural, stoichiometric, and compositional flexibility of perovskite photocatalyst materials. The photocatalytic activity of perovskite materials in different photocatalysis applications is also discussed. Various mechanisms involved in photocatalysis application from wastewater treatment to hydrogen production are also provided. The key objective of this review is to encapsulate the role of perovskite materials in photocatalysis along with their fundamental properties to provide valuable insight for addressing future environmental challenges.